Studies on Doctoral Theses in Agricultural Sciences of Rajasthan Agricultural University, Bikaner - Krishna, K. M. (Journal of Information and Knowledge, 2011)
Present study has been made to know the chronological distribution of theses, latest trends of research and average citation pattern per thesis, subject wise analysis of theses, types of documents used, gender wise submission of thesis, language wise study of cited documents and median citation age of cited books and journals by research scholars in agricultural sciences of Rajasthan agricultural university during 1996-2000. The present study based on PhD work of 68 theses of Rajasthan Agricultural University, Bikaner during 1996-2000 is being carried out in department of library science Ujjain (M P), India.